Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 956048 species occurrences available in GBIF matching the query: { "and" : [ "OccurrenceStatus is Present", { "or" : [ "TaxonKey is Brachypodium distachyon (L.) P.Beauv.", "TaxonKey is Brachiaria mutica (Forssk.) Stapf", "TaxonKey is Avena sterilis L.", "TaxonKey is Avena ludoviciana Durieu", "TaxonKey is Avena fatua L.", "TaxonKey is Avena barbata Pott ex Link", "TaxonKey is Arundo donax L.", "TaxonKey is Arrhenatherum elatius (L.) P.Beauv. ex J.Presl & C.Presl" ] } ] } The dataset includes 956048 records from 1138 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0218728-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences